EFL Teachers’ Readiness in Utilizing ICT in Blended Learning Class for Internship Students of Vocational High School in Indonesia - Alfiyati, Alfiyati (English Education Department STKIP Al Hikmah Surabaya, 2019)
This study aimed to explore the  readiness of Vocational High School English teachers who teach internship students by integrating ICT in blended-learning class and the obstacles faced by them. A survey was conducted involving all 100 teachers in vocational high school  in Kabupaten Pasuruan. The study informed the researchers that teachers were comfortable with the use of certain applications such as spreadsheet, presentation software, internet and e-mai, social media and event many free application in the handphone. The respondents demonstrated a positive attitude towards using ICT as majority of them used ICT for teaching and learning and felt that the connected classrooms can change the way students learn in classrooms. The study also explained that a connected classroom can be effective for students’ learning to happen. It was also found that the attitudes of teachers on use of ICT vary with their years of experience and level of knowledge on ICT.